2022
DOI: 10.1097/rhu.0000000000001822
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Outcomes in Idiopathic Inflammatory Myopathies

Abstract: BACKGROUNDIdiopathic inflammatory myopathies (IIMs) are chronic systemic autoimmune diseases defined by symmetrical, proximal muscle weakness, dysphagia, and interstitial lung disease (ILD). 1 Patients with IIM are predisposed to proinflammatory states, often immunocompromised by both their disease and medication regimens, and may have preexisting pulmonary conditions. Given these factors, it is imperative to review the outcomes of IIM patients with COVID-19 infections to anticipate the COVID-19 prognoses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Deposition of Hepatitis B antigen antibody complexes in muscle suggests a possible etiology linking Hepatitis B to Polymyositis as the triggering antigen [5]. This is also supported by the study done by Ana Valle et al which showed that Patients with HBV had a higher frequency of myositis-associated antibodies in comparison to patients without HBV [6]. Capasso et al revealed that the pathogenesis of myopathy is an immunemediated mechanism by demonstrating HBV DNA inside intact muscle fibers [7].…”
Section: Discussionmentioning
confidence: 78%
“…Deposition of Hepatitis B antigen antibody complexes in muscle suggests a possible etiology linking Hepatitis B to Polymyositis as the triggering antigen [5]. This is also supported by the study done by Ana Valle et al which showed that Patients with HBV had a higher frequency of myositis-associated antibodies in comparison to patients without HBV [6]. Capasso et al revealed that the pathogenesis of myopathy is an immunemediated mechanism by demonstrating HBV DNA inside intact muscle fibers [7].…”
Section: Discussionmentioning
confidence: 78%
“…The association between polymyositis and hepatitis B remain unclear, but the presence of antibody complexes against the hepatitis B antigen in muscle raises the possibility that link hepatitis B with polymyositis as triggering antigen [21]. It is also supported with the increase of myositisassociated antibodies found in patient with HBV infection more than patient without HBV infection [22]. Main treatment of polymyositis such as corticosteroid can cause suppression of Tcell cytotoxic which may lead to decrease immune ability against the virus and increase HBV-DNA replication through activation of corticosteroid-responsive transcriptional regulatory element which has been detected in HBV genome [9].…”
Section: Discussionmentioning
confidence: 99%